Studying Customer Satisfaction with Service Quality Using the Servqual Method: Case Study at PT. Federal International Finance East Surabaya Branch - Mahjudin Mahjudin; Muchammad Ilham Syaifullah A. M; Naurah Aurelia M (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The research for this thesis is entitled: